Nervous Necrosis Virus (NNV) Booster Vaccination Increases Senegalese Sole Survival and Enhances Immunoprotection - López-Vázquez, Carmen; Souto, Sandra; Olveira, José G.; Riaza, Ana; González, Óscar; Labella Vera, Alejandro Manuel (IOAP-MDPI, 2022)
Viral encephalopathy and retinopathy (VER), caused by nervous necrosis virus (NNV), is a serious threat to Senegalese sole farming. We have previously demonstrated that immunization with an inactivated vaccine confers partial protection against the infection. However, a vaccination program must be finely adjusted to achieve the best results in terms of immune system stimulation and protection. In this study we show that a booster injection 30 days after prime vaccination increases sole survival and reduces NNV replication in brain (viral target organ). The analysis of immune-related genes expression indicated that T CD4+ lymphocytes and the proteins Mx and HERC4 may play an important role in the protection. These findings increase our understanding of sole immune response against NNV and may contribute to the development of effective protection measures.
Keywords: Virus; Senegalese sole; Nervous necrosis virus (NNV); Re-immunization; Humoral response; Immune-related genes expression